Location selection of agricultural Machinery sheds for improved scheduling and efficiency under sustainability goals - Yang Liu; Xu Ma; Mingjun Jiang; Weilun Huang; Haisong Ren (Ecological Indicators, 2023)
The storage of agricultural machinery (AM) poses a critical operational challenge that requires attention to attain China's “Carbon Peaking and Carbon Neutrality” objectives, due to the carbon emissions and fuel consumption associated with AM operations. Nevertheless, this matter has not garnered adequate consideration. Existing studies have rarely focused on optimizing the parking locations for AM to mitigate emissions and advance sustainability. This study employs the TOPSIS-MCGP method to explore sustainable location selection for Chinese AM sheds. The principal factors influencing location selection include carbon emissions, fuel consumption, operational distance, total cost, and timeliness, which were thoroughly examined for their impact. A weighted selection approach was utilized to ascertain key factors and their optimization implications. The AM shed location within the AM dispatching system was developed through the following steps: (1) Evaluation of influential factors for sustainable AM dispatching, encompassing carbon emissions, fuel consumption rate, AM dispatching distance, cost, and timeliness. (2) Quantification of the manager's experience in the AM service center as an index weight using the Fuzzy Delphi Method (FDM). (3) Adoption of the TOPSIS-MCGP model to establish the relationship between operation points and AM shed locations during sustainable AM operations. A preliminary investigation was carried out in a company located in Harbin City, yielding an optimal solution encompassing a 13,500 mu working area, 3,300 total building area, and a 28-million RMB investment. The outcomes underscore the model's compatibility and its utility for optimizing sustainable AM service operations. In conclusion, this study underscores the significance of addressing AM storage to foster sustainability and emissions reduction. The TOPSIS-MCGP approach proves effective in selecting sustainable AM shed locations. By considering diverse factors like carbon emissions, fuel consumption, operational distance, total cost, and timeliness, companies can enhance their AM dispatching systems, contributing to China's “Carbon Peaking and Carbon Neutrality” ambition.